Toll-Like Receptor Homolog CD180 Expression Is Diminished on Natural Autoantibody-Producing B Cells of Patients with Autoimmune CNS Disorders. (25th May 2021) - Hayden, Zsófia; Erdő-Bonyár, Szabina; Bóné, Beáta; Balázs, Noémi; Bodó, Kornélia; Illes, Zsolt; Berki, Timea; Simon, Diána
Abstract : Purpose . Decreased expression of TLR homolog CD180 in peripheral blood B cells and its potential role in antibody production have been described in autoimmune diseases. Effectiveness of anti-CD20 therapy in neuromyelitis optica spectrum disorder (NMOSD) and multiple sclerosis (MS) strengthens the role of B cells in the pathogenesis. Therefore, we aimed to investigate the CD180 expression of peripheral blood B cell subsets in NMOSD and MS patients and analyze the levels of natural anti-citrate synthase (CS) IgG autoantibodies and IgG antibodies induced by bacterial infections reported to play a role in the pathogenesis of NMOSD or MS. Methods . We analyzed the distribution and CD180 expression of peripheral blood B cell subsets, defined by CD19/CD27/IgD staining, and measured anti-CS IgM/G natural autoantibody and antibacterial IgG serum levels in NMOSD, RRMS, and healthy controls (HC). Results . We found decreased naïve and increased memory B cells in NMOSD compared to MS. Among the investigated four B cell subsets, CD180 expression was exclusively decreased in CD19 + CD27 + IgD + nonswitched (NS) memory B cells in both NMOSD and MS compared to HC. Furthermore, the anti-CS IgM natural autoantibody serum level was lower in both NMOSD and MS. In addition, we found a tendency of higher anti-CS IgG natural autoantibody levels only in anti-Chlamydia IgG antibody-positive NMOSD and MS patients. Conclusions . Our results suggest that reduced CD180 expression of NS B cells could contribute to the deficient natural IgM autoantibody production in NMOSD and MS, whereas natural IgG autoantibody levels show an association with antibacterial antibodies.